2021
DOI: 10.1097/md.0000000000026885
|View full text |Cite
|
Sign up to set email alerts
|

Liver function tests as predictors of common bile duct stones in acute cholecystitis patients with a chronic history

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…6 Among CBD stones patients 71.1% were above 40 years of age group and 75.6% were female similar to findings in study by Zgheib H etal. 7 Similar demographic pattern was also seen by Song Y et al and Hosseini SV et alfrom China and Iran. Although there was a marked geographical variation in prevalence of biliary stone disease, it was more common in female and with increasing age of people.…”
Section: Discussionsupporting
confidence: 76%
“…6 Among CBD stones patients 71.1% were above 40 years of age group and 75.6% were female similar to findings in study by Zgheib H etal. 7 Similar demographic pattern was also seen by Song Y et al and Hosseini SV et alfrom China and Iran. Although there was a marked geographical variation in prevalence of biliary stone disease, it was more common in female and with increasing age of people.…”
Section: Discussionsupporting
confidence: 76%
“…Small-incision cholecystectomy, modified from traditional open surgery, reduces the surgical incision and the risk of infection [13] but is limited by its narrow intraoperative field. Clinical research has confirmed that laparoscopic cholecystectomy provides the larger Evidence-Based Complementary and Alternative Medicine surgical field and contributes to the rapid removal of the lesion, significantly shortens the operative time and postoperative hospital stay, and promotes postoperative recovery [14]. A study by Alexander et al suggested that laparoscopic cholecystectomy is less prone to medically induced injury to the gastrointestinal wall, greater omentum, and peritoneum during the operation and avoids intraoperative hemorrhage [15], and the closure of the gallbladder artery using an absorbable clip during the procedure significantly reduces intraoperative bleeding volume [16].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with GS combined with CBDS, significantly elevated levels of serum AST, ALT, and TBIL were observed. This finding may be attributed to the impact of artificial pneumoperitoneum during surgery on hepatic tissue hemodynamics and subsequent reduction in blood flow through the hepatic artery and portal vein leading to impaired liver function[ 28 ]. In addition, a meta-analysis found that CBDS was the most common etiology for significantly elevated ALT levels (> 500 IU/L), and that approximately one-third of patients with CBDS would present with ALT or AST > 500 IU/L[ 29 ].…”
Section: Discussionmentioning
confidence: 99%